PERANCANGAN PLTS SEBAGAI SUPLAI DAYA POMPA AIR TEMEGA PERUMDA TIRTA TOHLANGKIR KECAMATAN KARANGASEM - Andriantara, I Komang Bagus; Setiawan, I Nyoman; Sukerayasa, I Wayan (Jurnal SPEKTRUM, 2024)
This research discusses the design of Solar Power Plant (PLTS) as a power supply for Temega water pump Perumda Tirta Tohlangkir Karangasem District, Bali. The Temega water pump currently uses 11 kW of electrical power with high operational costs so that the PLTS is designed to reduce dependence on PLN electricity and reduce operational costs. This research focuses on the results of simulation analysis of scenarios 1, 2, and 3 using PVSyst software. Simulation scenario 1 uses 48 solar modules (16 in series and 3 in parallel) to meet the daily energy demand of 26.64 kWp pump. Scenario 2 simulation uses 30 solar modules (15 in series and 2 in parallel) to meet the daily energy demand of 16.65 kWp pumps. Simulation scenario 3 uses 26 solar modules (13 in series and 2 in parallel) to meet the daily energy needs of the pump of 14.43 kWp. The results show that scenario one simulation produces the highest energy but causes an energy surplus, while scenarios two and three are more efficient in minimizing wasted energy, which is 0 kWh/year.